1,1-Diphenyl-2-picrylhydrazyl radical scavenging activity of novel dihydropyridine derivatives - Anwar, Ayaz; Hameed, Abdul; Perveen, Shahida; Uroos, Maliha; Choudhary, Muhammad Iqbal; Basha, Fatima Zahra (European Journal of Chemistry, 2014)
Thirteen dihydropyridine analogues 1-13 were synthesized and evaluated for their DPPH radical scavenging activity. A good to moderate antioxidant activity ranging from 127.4 to 284.5 μM was observed and structure-activity relationship was established. The 3’-fluoro derivative 8 (IC50 = 127.4±3.5 μM) was found to exhibit highest activity among the dihydro pyridine derivatives 1-13, while the other derivatives 11 (IC50 = 132.5±3.32 μM), 6 (IC50 = 142.2±0.60 μM), 10 (IC50 = 144.7±2.46 μM), 12 (IC50 = 153.7±0.50 μM), 5 (IC50 = 161.4±2.81 μM) and 5 (IC50 = 164.4±2.50 μM) possess moderate activity, depends upon the C-4 and C-6 substituted groups. The compounds 7, 13, 4, 3 and 2 have lowest IC50 values, ranging between 172.8 and 284.5 μM. Dihydropyridine analogues were characterized by spectroscopic techniques.